Exploring the relationship between obesity and the probability of gaining employment in the context of the South African labour market - von Widdern, Chloe (School of Economics, 2022)
Obesity is a growing public health concern that is being confronted by both developed and developing countries. South Africa is no exception, facing the highest burden of obesity amongst African countries. Using two waves of data from the National Income Dynamics Study, this study aims to investigate the relationship between obesity and employment status for working age individuals in the context of the South African labour market. This study contributes to existing literature on this subject by explicitly accounting for potential simultaneity and endogeneity between obesity and employment. Given the hypothesised two-way causal relationship between obesity and unemployment, two different models are used to assess whether this issue exists for the dataset; a bivariate probit model to assess if there is a bivariate relationship between obesity and employment, and a recursive bivariate probit model to assess if obesity is an endogenous regressor of employment. A change in state univariate probit model is then implemented across the two waves to better understand if fluctuations in weight status are a result of labour market state transitions. The results of the study show that obesity and employment are independent in the bivariate probit models and obesity is an exogenous regressor of employment status in the recursive bivariate probit models. Changes in labour market state do not have a significant impact on the probability of transitioning to obese compared to no changes in labour market state, bar transitioning from not economically active to employed, which increases the probability of becoming obese. The findings suggest that, in the South African labour market context, obesity and employment are not related, indicating that there are other underlying factors, such as nutritional intake and genetic composition, that may contribute to fluctuations in weight status. The results suggest that obesity is prolific in South Africa, and impacts individuals across the entire distribution for labour market status and income.